Implementasi Penyetaraan Jabatan Dalam Pengembangan Karier Pejabat Fungsional Di Lingkungan Pemerintah Kota Bekasi - Massepe, A. Pangerang Batara Bau; Daraba, Dahyar; Sinurat , Marja (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
This research was conducted with the aim of knowing and analyzing the implementation of equal positions in the career development of functional officials, the factors inhibiting the implementation of equal positions in the career development of functional officials, and the efforts made to overcome obstacles to the implementation of equal positions in the career development of functional officials within the Bekasi City Government. The research method used in this research uses a descriptive qualitative method using policy implementation theory using George Edward III's theory, namely the communication dimension, resource dimension, disposition dimension and bureaucratic structure dimension. Furthermore, the data collection method used used in-depth interviews, observation and documentation. then the data analysis technique used uses data reduction, data presentation and drawing conclusions.The research results show that the implementation of equalization of positions in the career development of functional officials within the Bekasi City Government has not gone well and optimally. This is indicated by problems still being found regarding the lack of dissemination of information regarding career development policies as a whole to all supervisory officials and administrator officials who are affected by equalization into functional positions. Then there is neglect of competency and qualification tests in the job equalization process which has the potential to violate the principles of career patterns, namely the principles of certainty and professionalism. Apart from that, there is a lack of accommodating career certainty for functional equalization officials, where functional equalization positions are still found that do not have a position level above them, where there are no functional equalization officials who fill the functional position level above them. In an effort to overcome obstacles, the Bekasi City Government opened a consultation room through the implementation of FGD (Forum Group Discussion), facilitating the development of competency and qualifications for functional officials and increasing the number of Functional Position boxes.Suggestions given in this research, 1. The Bekasi City Government through BKPSDM should improve communication and outreach regarding career development policies after bureaucratic simplification; 2. The Bekasi City Government, through BKPSDM, should identify and carry out mapping and prepare plans for competency and qualification improvement needs along with financing for equalization functional positions based on the mapping results; 3. The Bekasi City Government, through the SETDA Organizational Section, should be proactive in facilitating proposals for the opening of new functional positions to accommodate the career paths of equalization functional officials so that they can support and contribute to performance achievements in Regional Apparatus.